Elements of singing in Arabic song From the viewpoint of specialized (Journal of the College of Basic Education, 2022)
The musical heritage of the Arab music is characterized by diversityin the multiple forms of music, and this diversity to make each style ofsinging or musician features and components are different from otherforms of parallel events, such as etched, the anthem or hymns or song orsongs enthusiastic children or work songs, all these patterns have featuresand elements of recognized standards, either inherent in the dominantcharacteristic of Arabic music and singing are singing feature, this featurefound in most forms, song and music,